2016
DOI: 10.1074/jbc.m115.679167
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Zinc Finger Protein ZRANB2 as a Novel Maternal Lipopolysaccharide-binding Protein That Protects Embryos of Zebrafish against Gram-negative Bacterial Infections

Abstract: Zinc finger ZRANB2 proteins are widespread in animals, but their functions and mechanisms remain poorly defined. Here we clearly demonstrate that ZRANB2 is a newly identified LPSbinding protein present abundantly in the eggs/embryos of zebrafish. We also show that recombinant ZRANB2 (rZRANB2) acts as a pattern recognition receptor capable of identifying the bacterial signature molecule LPS as well as binding the Gramnegative bacteria Escherichia coli, Vibrio anguilarum, and Aeromonas hydrophila and functions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…As reported previously by Wang et al (21), band a on SDS‐PAGE ( Fig . 1 A ) of the proteins eluted from the LPS‐conjugated Sepharose CL‐4B column was ZNF365 (GenBank accession number XP_001339691.1), consisting of 345 aa.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…As reported previously by Wang et al (21), band a on SDS‐PAGE ( Fig . 1 A ) of the proteins eluted from the LPS‐conjugated Sepharose CL‐4B column was ZNF365 (GenBank accession number XP_001339691.1), consisting of 345 aa.…”
Section: Resultssupporting
confidence: 80%
“…The cloning of znf365 was conducted as described by Wang et al (21). Primer pair P1 and P2 ( Table 1 ), specific for znf365 , was designed using Primer Premier 5.0 (Premier Biosoft, Palo Alto, CA, USA) on the basis of the sequence of zebrafish znf365 (XM_001339655.4) in the National Center for Biotechnology Information database.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data hint a clue that Ly2.1–3 may function as pattern recognition molecules capable of identifying the Gram-negative bacteria. Recently, Wang et al [29] identified the zinc finger protein ZRANB2 as a novel maternal LPS-binding protein that protects embryos of zebrafish against Gram-negative bacterial infections and they also found rZRANB2 can bind to lipid A, a core component of LPS, and the affinity of rZRANB2 to LPS was not inhibited by any of the sugars examined. We do not know the mechanism why Ly2.1–3 only targets Gram-negative bacteria, whereas rZRANB2 and rLy2.1–3 all can bind to LPS but not to LTA.…”
Section: Discussionmentioning
confidence: 99%